Environmental benefits and impact assessment of oats in the UK - Valentine, John; Cowan, Sandy (MTT, 2004)
As part of an application for a Sustainable Arable LINK on the incorporation of important traits underlying sustainable development of the oat crop (in which the Government part funds industrially relevant research to further its policy objectives), we undertook a short Environmental Impact Assessment summarising the impact of current practices and expected project outputs for diverse indicators. Results are summarised here. Oats receive 0.15kgs/ha of fungicides (wheat 0.58); 0.78 herbicides (2.23); 0.01 insecticide (0.05); 0.89 PGR (1.17); 0.01 molluscides (0.12);total 1.84 (4.15) (Garthwaite and Thomas, 2003). Improved lodging resistant dwarf oats would reduce the risk of plant growth regulators residues in oat products. Oats have been shown to be more nitrogen (N) efficient than wheat, with a lower risk of N pollution of watercourses. Typical N balances (Sylvester- Bradley 1993) are 95kg/ha offtake from 100kg/ha applied compared to 135kg/ha offtake from 200kg/ha applied for wheat. Lower inputs and gas emissions are associated with lower number of sprayer rounds with obvious reductions in fuel consumption and greenhouse gas emissions. A return to mixed farming would have a positive effect on populations of farmland birds, rare arable weeds and the brown hare. Within the rural economy, oats are a profitable break crop valuable in rotations, and the rate of progress in national yields of oats is similar to that of wheat and exceed those of barley. We conclude that the demand for more oats as a result of expanding existing markets or creating new markets would bring impressive benefits to sustainable agriculture. Garthwaite DG, Thomas MR, Dawson A and Stoddart H. 2002. Pesticide Usage Survey Report 187. Arable Crops in Great Britain, Defra and Seerad. http://www.csl.gov.uk/science/organ/pvm/puskm/arable2002.pdf;Sylves ter Bradley R. 1993. Proceedings of the cereals R&D conference. Home Grown Cereals Authority. Robinson College, Cambridge 5,6 January 1993 pp 198-217.
Keywords: Ka; oats; environment; pesticides; biodiversity; indicators